The battle against internet trolls shows that a compelling story will always beat cold, hard facts. - Lewis, Helen (New Statesman, 2014)
The author discusses Internet-trolling and misogyny, focusing on her view that harassment is justified through narrative. Topics include a discussion of women who have been the victim of hate speech after becoming successful on the Internet, such as Kathy Sierra, Mary Beard and Anita Sarkeesian; a discussion of the way trolls turn the narrative from harassment to standing up for their rights; and the Digital Millennium Copyright Act.